Perceived Impact of Modern-Day Inflation on the Budget Consumption and Decisions of Senior High School Learners - Lastimosa, Robert Julius; Hornada, Jasmine Kate; Sedik, Ayessa Leigh B.; Gaygay Jr. , Carlos Friales (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
nflation has affected numerous aspects of living globally, and this consistent drop in purchasing power has been attributed to the rise of overall prices of goods, leading to greater challenges in global living standards. There have been numerous studies indicating the impact of inflation amongst many stakeholders, but in this study, the objective is to assess whether it also affected the learners of a selected institution in the same way. Hence, a descriptive-correlational design was utilized to describe and correlate the levels of perceived assessment on modern-day inflation and the perceived changes in the budget consumption and decisions of Senior High School learners in the period of 2022. A structured Likert scale survey questionnaire adopted from the study of Avila & Gatpolintan (2019) was distributed to a sample of 282 respondents using simple random sampling. The data were analyzed using descriptive statistics for the first two objectives and Pearson r correlation for the third. The study revealed a very high level of agreement in the price increase brought by their perceptions toward modern-day inflation, a very high level of agreement on their perceived changes toward expenditures, and a high level for their preferences and quantity of consumption. The study also noted a moderate positive correlation (p<0.05) between the two variables, indicating that the learners' budgeting behaviors are influenced by their assessment of rising prices and that their perceptions have also been influenced by how they chose and quantified their necessities, respectively.